2010
DOI: 10.1007/s10726-010-9203-9
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating Loosely-Coupled Work in Construction Inspection Activities

Abstract: Artículo de publicación ISIInspections represent key activities in construction projects. They allow coordinating the work of the main contractor and the subcontracted companies participating in the project. Today the inspection activities and the coordination process are done using information recorded into paper-based blueprints. As a consequence of it, coordinating the activities derived from inspection processes become expensive, slow and error-prone. This paper presents a mobile shared workspace, named CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We can thus argue that in such a situation, with the need to engage in ad hoc, unanticipated, and thus temporally unstructured work (task fluidity), the mobility afforded by their work devices enables them to engage meaningfully in such activities. It is notable that the affordance of mobility allows workers to be loosely coupled to each other, in essence promoting autonomous and on-demand collaboration [84], which we have already alluded to.…”
Section: Antecedents To Task Fluidity: Connectedness Interoperabilitmentioning
confidence: 96%
“…We can thus argue that in such a situation, with the need to engage in ad hoc, unanticipated, and thus temporally unstructured work (task fluidity), the mobility afforded by their work devices enables them to engage meaningfully in such activities. It is notable that the affordance of mobility allows workers to be loosely coupled to each other, in essence promoting autonomous and on-demand collaboration [84], which we have already alluded to.…”
Section: Antecedents To Task Fluidity: Connectedness Interoperabilitmentioning
confidence: 96%
“…A review of the foreign and domestic literature revealed an increase in the use of mobile devices in construction in recent years; such devices make the management of documents more convenient and increase construction efficiency. Ochoa et al (2011) developed COIN (Construction Inspector), a document-sharing workspace with functions that include the management of inspection tasks associated with various construction tasks, the viewing and marking of construction drawings, and synchronous construction data messaging. Nguyen et al (2015) created the InSite Inspector application, whose functions include recording information that is associated with construction errors, the automatic GPS-based location of such errors, and reporting the results of inspections.…”
Section: Applications Of Mobile Devices In Constructionmentioning
confidence: 99%
“…Advances in mobile computing and wireless communications have created a shift in the development of collaborative applications from a mainly stationary focus to more dynamic contexts and mobile forms of collaboration. This have been the case for a large number of application domains, such as design [243], healthcare [220], construction work [172], emergency management [155], productive activities [164] and education [47,226,57,218,60,194], this last being considered as one of the main application areas.…”
Section: Manets In Collaborative Learningmentioning
confidence: 99%
“…stationary collaboration scenario) held by the medical staff. Similarly, [172] reports meetings held by construction inspectors in the field after an inspec- In a stationary collaboration scenario, mobile users are static while performing a collaborative activity. Typically, if mobile users need to see their devices' screens in order to collaborate, then they usually stop moving because the focus of their attention is now on the screens instead of on their steps.…”
Section: Experimentation Scenariosmentioning
confidence: 99%
See 1 more Smart Citation